Madre o progenitora: qué dice el psicoanálisis - Jaramillo Romero, Lady Vanessa (My University, 2021)
The term mother for medicine would be linked to the woman who begets, but when referring to the mother from psychology it is to go beyond the biological, it is to focus on the subject that supplies the basic needs of the infant, based on this idea, a bibliographic review has been carried out for this essay with the topic: Mother or progenitor. What does psychoanalysis say for which a compilation of information from scientific articles and the analysis of a case has been made. This study is focused on answering the question: Why is it believed that fathering a subject makes a mother? From this question, the search for information has been directed, understanding with this that there is a social imaginary that is directly related between motherhood and femininity, from this idea, it is intended to show that motherhood is not only inherent to women, but also, It can be attributed to another subject that fulfills the maternal function that will be exposed in this writing.
El término madre para la medicina sería ligado a la mujer que engendra, pero al referirnos a la madre desde la psicología es ir más allá de lo biológico, es centrarse en el sujeto que suple las necesidades básicas que tenga el infante, a partir de esta idea, se ha realizado para este ensayo una revisión bibliográfica con el tema: Madre o progenitora. Qué dice el psicoanálisis para lo cual se ha hecho una recopilación de información de artículos científicos y el análisis de un caso. Este estudio está enfocado en contestar a la pregunta ¿Por qué se cree que engendrar a un sujeto convierte en madre? Desde esta pregunta se ha direccionado la búsqueda de información, comprendiendo con ello que existe un imaginario social que se relaciona directamente entre la maternidad con la feminidad, desde esta idea, se pretende demostrar que la maternidad no sólo es inherente a la mujer, sino también, puede atribuirse a otro sujeto que cumpla con la función materna que se expondrá en este escrito.
Keywords: MADRE; FUNCION MATERNA; HOMOPARENTAL; LEGALIZACION ABORTO